(untitled) (Research, Society and Development, 2021)
Objective: The study in question aimed to identify digital fluency through the use of the questionnaire, from Piconez in nursing undergraduates. Method: Study of cross-sectional, quantitative approach, composed of 91 undergraduate students distributed between the 1st to the 5th semester of the nursing course. Data were collected in April 2019. A form containing the sociodemographic data and the Piconez Instrument was applied. The data were presented descriptively. The project was submitted to Plataforma Brasil under the number CAEE 89610218.1.0000.5493. Result: The predominant variable was 68% female and 23% male. When analyzed in the semester, 24% were from the 5th semester, 22% from the 1st semester, 17% from the 2nd and 4th semester, 10% from the 3rd semester and 1% null. Conclusion: The use of technology in the hybrid modality opens precedents and gaps to be explored and mobilized for use as teaching strategies. In this perspective, it brings innovations to be used and implemented with regard to the pedagogical approach as a mediator of knowledge and learning.